Osteosarcoma immunometabolism: emerging mechanisms and clinical implications - Tan, Bowen; Ning, Jingyuan (Frontiers in Immunology, 2025)
Osteosarcoma (OS) is the most common primary malignant bone tumor, predominantly affecting adolescents and young adults. Despite decades of research, survival rates for metastatic or recurrent disease remain dismal, underscoring the urgent need for therapeutic innovation. This malignancy frequently exhibits refractory responses to immunotherapy, a limitation increasingly attributed to dysregulated immunometabolic crosstalk. Growing evidence supports cellular metabolism as a master regulator of both neoplastic progression and immune cell functionality. To meet heightened biosynthetic demands, OS cells undergo metabolic reprogramming, adopting distinct programs divergent from normal counterparts. These changes reshape the tumor microenvironment (TME) into an immunosuppressive milieu, restricting immune cell infiltration and effector activity. Consequently, targeting these immunometabolic pathways offers a promising strategy to overcome therapeutic resistance. Here, we critically analyze the current understanding of OS immunometabolism, systematically delineating OS-specific evidence from extrapolated concepts. We dissect the key metabolic barriers to successful immunotherapy and propose a forward-looking roadmap to guide the development of more effective, biomarker-driven therapeutic strategies.